1993
DOI: 10.4319/lo.1993.38.8.1615
|View full text |Cite
|
Sign up to set email alerts
|

Egg viability in the copepod Temora stylifera

Abstract: Estimates of production rate and viability of eggs are reported for Remora styIzj2ra collected in the Bay of Naples (Italy). Complementary observations on rates of fecal pellet and spcrmatophore production and female longevity were also conducted during the incubations. In situ egg viability was highly variable during the 2 yr of observation, with mean monthly values of ~80% of total egg production. Under experimental food-saturated conditions, the nature and hatching success of eggs were modified depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 26 publications
(43 reference statements)
4
85
3
2
Order By: Relevance
“…This is not surprising because it is known that the chemical composition of freshly spawned copepod eggs is sensitive to the maternal diet (Guisande & Harris 1995, Guisande et al 1999, Laabir et al 1999. For this reason, reduced hatching success in copepods has been associated with nutritional inadequacy (Ianora et al 1992, Ianora & Poulet 1993, Guisande et al 1999, Laabir et al 1999 or inhibitors (see Ban et al 1997). Moreover, this study has also shown that nauplii hatched from females fed non-toxic food reached the copepodite stage earlier than nauplii hatched from females fed toxic food.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because it is known that the chemical composition of freshly spawned copepod eggs is sensitive to the maternal diet (Guisande & Harris 1995, Guisande et al 1999, Laabir et al 1999. For this reason, reduced hatching success in copepods has been associated with nutritional inadequacy (Ianora et al 1992, Ianora & Poulet 1993, Guisande et al 1999, Laabir et al 1999 or inhibitors (see Ban et al 1997). Moreover, this study has also shown that nauplii hatched from females fed non-toxic food reached the copepodite stage earlier than nauplii hatched from females fed toxic food.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic Nodularia spumigena is low-quality food for copepods (Sellner et al 1996, Schmidt & J贸nasd贸ttir 1997, Koski et al 1999a, which is in accordance with our findings on low pellet production rates on this species. In contrast, Ianora & Poulet (1993) suggested that pellet production increases on low-quality diet because bad food can neither be properly assimilated nor transferred into production. Some studies have also suggested that low-quality food may be fed at a high rate to attain enough essential elements and energy for maintenance and growth, i.e.…”
Section: Pellet Productionmentioning
confidence: 99%
“…Mar Ecol Prog Ser 216: [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165] 2001 Some studies have found consumption of diatoms by females to result in low hatching success (Ianora & Poulet 1993, Poulet et al 1994, Chaudron et al 1996, Ban et al 1997), but this is still open to discussion (J贸nasd贸ttir & Ki酶rboe 1996, J贸nas-d贸ttir et al 1998, Irigoien et al 2000b.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%